2018
DOI: 10.1111/1365-2745.13112
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity correlated with above‐ground biomass production during forest succession: Evidence from tropical forests in Southeast Asia

Abstract: 1. Enhancing knowledge on the role of evolutionary history during forest succession and its relationship with ecosystem function is particularly relevant in the context of forest landscape restoration for climate change mitigation and adaptation.2. We used fine resolution vegetation and environmental data (soil, elevation and slope) from two large-scale surveys (320 × 1000 m 2 plots in two 10 km × 10 km blocks) in the Upper Mekong to quantify (1) the role of abiotic and biotic (species interactions) factors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 113 publications
(145 reference statements)
9
35
2
Order By: Relevance
“…Both taxonomic and evolutionary diversity had no effect on aboveground biomass in intact forests in Amazonia. These results are supported by a previous pan-tropical study that used an overlapping dataset to investigate the role of taxonomic diversity on biomass 26 , and a recent study that investigated the role of evolutionary diversity on biomass during forest succession and found that despite a positive effect of phylogenetic diversity on biomass in early successional forests, there is no effect at later stages of forest succession 45 . Not surprisingly, but contrary to the positive effect of taxonomic and evolutionary diversity on productivity, biomass was strongly determined by functional characteristics (Figure 3; Supplementary Table 5), with variation in wood density being the most important variable in controlling patterns of biomass in these forests 15,26,46 .…”
Section: Discussionsupporting
confidence: 77%
“…Both taxonomic and evolutionary diversity had no effect on aboveground biomass in intact forests in Amazonia. These results are supported by a previous pan-tropical study that used an overlapping dataset to investigate the role of taxonomic diversity on biomass 26 , and a recent study that investigated the role of evolutionary diversity on biomass during forest succession and found that despite a positive effect of phylogenetic diversity on biomass in early successional forests, there is no effect at later stages of forest succession 45 . Not surprisingly, but contrary to the positive effect of taxonomic and evolutionary diversity on productivity, biomass was strongly determined by functional characteristics (Figure 3; Supplementary Table 5), with variation in wood density being the most important variable in controlling patterns of biomass in these forests 15,26,46 .…”
Section: Discussionsupporting
confidence: 77%
“…For example, previous work has found that functional and species diversity at local scales promotes biomass and tree growth ( Barrufol et al, 2013 ; Liang et al, 2016 ). Similar findings have been reported for phylogenetic diversity at local scales ( Satdichanh et al, 2019 ). Especially when combining with species data, using the crown data to investigate the scale and strength of these effects will inform the mechanisms of community assembly, ecological stability, and forest productivity.…”
Section: Discussionsupporting
confidence: 89%
“…For example, previous work has found that functional and species diversity at local scales promotes biomass and tree growth (Barrufol et al, 2013; Liang et al, 2016). Similar findings have been reported for phylogenetic diversity at local scales (Satdichanh et al, 2019). Especially when combining with species data, using the crown data to investigate the scale and strength of these effects will inform the mechanisms of community assembly, ecological stability and forest productivity.…”
Section: Evaluation and Validationsupporting
confidence: 89%